Performance analysis of video call SIP and SIP-TLS in different LAN environments / Zulkarnain Zainal - Zainal, Zulkarnain (2007)
The commercial deployment of VoIP necessitates the employment of security mechanisms that can ensure availability, reliability, confidentiality and integrity. The Session Initiation Protocol (SIP) is considered as the dominant signaling protocol for calls over the Internet. SIP, like other Internet protocols, is vulnerable to known Internet attacks, while at the same time it introduces new security problems in the VoIP system. This paper will describe SIP video call to a level that allows discussion of security issues and concerns. The increasing of high speed network development make VoIP implement growth in the internet telephony bringing connectivity to portable, instant on devices. Nowadays business really concerns implements VoIP, component of VoIP system, and relevant security issues in VoIP. So this project will concern not only the analysis on how to secure SIP video call but also the effect on quality of services (QoS). This paper studies transmission SIP video call using a specific software client installed in the Laptop. The software clients will connect to our development secure SIP server. This research also conducts an analysis of SIP video for the quality performance using the Laptop over wireless and wired. This research also makes comparison between implementation SIP video call over secure channel and none secure channel networks. A simulation of small VoIP environment was created to analyze the SIP video call performance.